Adaptive policies for short-term material flow optimization in a mining complex. Issue 1 (2nd January 2018) - Paduraru, Cosmin; Dimitrakopoulos, Roussos
Abstract: With the advent of inexpensive sensors and digital storage, increasing amounts of data about a mining complex can be collected. This data can, in turn, be used to continuously adapt stochastic optimization models and short-term mining decision making, thus reducing and managing local uncertainty. Taking advantage of this uncertainty reduction requires new decision-making approaches, mechanisms, and optimization methods. This paper proposes the use of state-dependent policies, which encode recipes for responding to new information as it comes along. Focusing on short-term planning shows how to represent and optimize state-dependent policies for making adaptive destination decisions for materials mined and processed. Resulting policies can be applied across different short-term time scales, marking an important step towards simultaneously optimizing different time scales. An implementation of the proposed method at a copper-gold deposit shows that it can improve the utilization of processing streams, production and financial performance over simple heuristic approaches and practices.